Il ruolo e la posizione del traduttore letterario nel XXI secolo Traduttore letterario − il mediatore tra le culture - Tomasi-Kapral, Elżbieta (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The 21st century is the age of migration. We observe right now how many people leave their homelands (due to wars and economic situation) and move out to live in places where they cannot communicate using their native language. Therefore the 21st century shall be the age of globalization, formation of multicultural and multilingual societies, giving the newcomers an opportunity to create a new reality. Europe will have to confront with numerous difficulties such as, for instance, creating a space where diversity will not bring about fears or discrimination. On the contrary, it will be accepted and respected. For such a reason there is more and more discussion about cultural exchange. Undoubtedly, one of the windows to look at another culture is literature. The European Commission supports, in recent years, projects focused on literary translation, co-financing the work of translators and their education among the so-called young professionals. Both social and professional position of translators becomes a hot issue of public discussions. It is not an accidental act – together with the changing reality, the role and position of the literature translators in the contemporary world must be redefined. The literary translation brings many benefits and that is the object of this article.